21st century sociology a reference handbook - Bryant, Clifton D., 1932-; Peck, Dennis L. (Thousand Oaks, Calif. ; London : SAGE, 2007)
'21st Century Sociology' provides a forum through which the vast array of knowledge accumulated can be organised into a definitive resource. The two volumes focus on the knowledge garnered in traditional areas of sociological inquiry, as well as document the general orientation of the emerging areas of sociological inquiry.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Sociology